ONS WAS DAAR (WE WERE THERE) - Scholtz, Leopold (Scientia Militaria - South African Journal of Military Studies, 2012)
Judging by the number of books published – either on paper or on the internet – the (probably mostly white) public’s interest in the so-called Border War is ostensibly at an all-time high. By far most of the publications are written by ex-soldiers who themselves participated in the war, but academics are also increasingly turning their attention in that direction.